Fatal disseminated strongyloidiasis after kidney transplantation - Ferreira,Carla Juliana Araújo (2012)
Disseminated strongyloidiasis (DS) is a rare and severe parasitic disease that is difficult to recognize and affects immunocompromised individuals. We report the case of a kidney transplant recipient who presented with DS despite prophylaxis with albendazole. We have discussed the need for better prophylactic strategies and for a higher degree of suspicion in order to diagnose DS.